Quantitative vessel mapping on increment cores: a critical comparison of image acquisition methods - Peters, Richard L.; Klesse, Stefan; Van den Bulcke, Jan; Jourdain, Lisa M. Y.; von Arx, Georg; Anadon-Rosell, Alba; Krejza, Jan; Kahmen, Ansgar; Fonti, Marina; Prendin, Angela Luisa; Babst, Flurin; De Mil, Tom (Frontiers in Plant Science, 2025)
IntroductionQuantitative wood anatomy is critical for establishing climate reconstruction proxies, understanding tree hydraulics, and quantifying carbon allocation. Its accuracy depends upon the image acquisition methods, which allows for the identification of the number and dimensions of vessels, fibres, and tracheids within a tree ring. Angiosperm wood is analysed with a variety of different image acquisition methods, including surface pictures, wood anatomical micro-sections, or X-ray computed micro-tomography. Despite known advantages and disadvantages, the quantitative impact of method selection on wood anatomical parameters is not well understood.MethodsIn this study, we present a systematic uncertainty analysis of the impact of the image acquisition method on commonly used anatomical parameters. We analysed four wood samples, representing a range of wood porosity, using surface pictures, micro-CT scans, and wood anatomical micro-sections. Inter-annual patterns were analysed and compared between methods from the five most frequently used parameters, namely mean lumen area (MLA), vessel density (VD), number of vessels (VN), mean hydraulic diameter (Dh), and relative conductive area (RCA). A novel sectorial approach was applied on the wood samples to obtain intra-annual profiles of the lumen area (Al), specific theoretical hydraulic conductivity (Ks), and wood density (ρ).ResultsOur quantitative vessel mapping revealed that values obtained for hydraulic wood anatomical parameters are comparable across different methods, supporting the use of easily applicable surface picture methods for ring-porous and specific diffuse-porous tree species. While intra-annual variability is well captured by the different methods across species, wood density (ρ) is overestimated due to the lack of fibre lumen area detection.DiscussionOur study highlights the potential and limitations of different image acquisition methods for extracting wood anatomical parameters. Moreover, we present a standardized workflow for assessing radial tree ring profiles. These findings encourage the compilation of all studies using wood anatomical parameters and further research to refine these methods, ultimately enhancing the accuracy, replication, and spatial representation of wood anatomical studies.